A genome-wide association study on mechanisms underlying genetic resistance to gastrointestinal parasites in goats, Zimbabwe - Zvinorova, Plaxedis I. (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhDAgric)--Stellenbosch University, 2017.